Molecular cloning of gene sequences regulated by tumor promoters and mitogens through protein kinase C. - Johnson, M D (1987)
cDNA clones representing genes whose expression is modulated by treatment with mitogens and tumor promoters were isolated and characterized. TPA-S1 corresponds to an mRNA species whose abundance was increased markedly within 1 h of exposure to the tumor promoter 12-O-tetradecanoyl phorbol-13-acetate (TPA), and TPA-R1 represents an mRNA that was decreased in TPA-treated cells. The induction of TPA-S1 was blocked by actinomycin D but was not affected by cycloheximide, and it was specific for phorbol esters with tumor-promoting activity. The role of protein kinase C in the induction of TPA-S1 is supported by the following lines of evidence. (i) Agents that activated protein kinase C (TPA, platelet-derived growth factor, and diacylglycerol) also increased TPA-S1 mRNA levels. (ii) A potent PKC inhibitor blocked the induction of TPA-S1. (iii) Down-regulation of PKC activity, by treatment of cells with TPA for 24 h, resulted in a loss of responsiveness to TPA-S1 induction by subsequent TPA treatment. DNA sequence analysis of TPA-S1 predicts a cysteine-rich, secreted protein with a molecular weight of 22.6 X 10(3) that exhibits homology with sequences representing a protein with human erythroid-potentiating activity and protease inhibitory activity.